PDBe: towards reusable data delivery infrastructure at protein data bank in Europe. Issue Volume 46:Issue D1(2018) (6th November 2017) - Mir, Saqib; Alhroub, Younes; Anyango, Stephen; Armstrong, David R; Berrisford, John M; Clark, Alice R; Conroy, Matthew J; Dana, Jose M; Deshpande, Mandar; Gupta, Deepti; Gutmanas, Aleksandras; Haslam, Pauline; et al.
Abstract: The Protein Data Bank in Europe (PDBe, pdbe.org) is actively engaged in the deposition, annotation, remediation, enrichment and dissemination of macromolecular structure data. This paper describes new developments and improvements at PDBe addressing three challenging areas: data enrichment, data dissemination and functional reusability. New features of the PDBe Web site are discussed, including a context dependent menu providing links to raw experimental data and improved presentation of structures solved by hybrid methods. The paper also summarizes the features of the LiteMol suite, which is a set of services enabling fast and interactive 3D visualization of structures, with associated experimental maps, annotations and quality assessment information. We introduce a library of Web components which can be easily reused to port data and functionality available at PDBe to other services. We also introduce updates to the SIFTS resource which maps PDB data to other bioinformatics resources, and the PDBe REST API.